Association Between Physician Density and Life Expectancy Across 58 Countries Using 2023 International Health Data - Sabrina Intan Zoraya; Sabariah Sabariah (Jurnal Ners, 2026)
Physician density is a key indicator of health system capacity and has been associated with various population health outcomes, including life expectancy. However, updated global evidence using recent data remains limited. This study aimed to examine the association between physician density and life expectancy across countries using the most recent available data from 2023. A cross-sectional ecological study was conducted using secondary data from the World Health Organization, the Organisation for Economic Co-operation and Development, and the World Bank. A total of 58 countries were included based on data availability. Physician density (per 1,000 population) was analyzed as the independent variable, while life expectancy at birth (years) was the dependent variable. The analysis showed a strong positive association between physician density and life expectancy. Pearson correlation yielded r = 0.771 (p < 0.001), while Spearman correlation showed ρ = 0.827 (p < 0.001). Physician density is strongly associated with life expectancy at the country level. These findings highlight the importance of strengthening the health workforce as part of efforts to improve population health outcomes. Policies aimed at increasing and equitably distributing physicians may contribute to gains in life expectancy, particularly in countries with limited healthcare access.